Knowledge, attitude and practice regarding prevention and control of communicable diseases in children among child care workers and parents, 2017 - เลิศสุโภชวณิชย์, สมนึก; ผดุงหมาย, มัลลิกา; นาคอ้าย, วรยุทธ; อยู่เจริญ, พรศักดิ์ (Disease Control Journal, 2018)
This cross-sectional survey was aimed to describe the 3 core behavioral factors; knowledge, attitude and practice of the child care workers and parents on prevention and control of communicable diseases among children. From November 2016 to March 2017, 276 child care workers and 999 parents were included in the study by Multi-stage sampling from 12 health care facilities in 12 provinces in 12 health regions. Each health region used simple random method that run by provinces, districts and child care centers in Thailand. Data were collected by self-administrative questionnaires and analyzed by using a descriptive and deductive statistics. In the child care workers, they had good score level of knowledge, attitude and practice. The results of correlation analysis showed that knowledge and practice scores on prevention and controlling of communicable diseases were significantly correlated with the experience of child care training (p<0.05). The practice score on prevention and controlling on communicable diseases was significantly correlated with child care workers who had been trained, ever received a supervision, and had educational tour related to prevention of communicable diseases among children (p<0.05). The parents had fair level of knowledge score, good level of attitude and practice score. The results of correlation analysis showed that parents’ knowledge score on prevention and controlling communicable diseases was significantly correlated with parents who ever received the information related to respiratory tract diseases, diarrhea diseases, hand-foot-mouth diseases, and parents whose their child had a history of respiratory tract infection (p<0.05). The practice scores on prevention and controlling of the communicable diseases among the children was significantly correlated with experiences on child care training (p<0.05). In order to control communicable diseases among children, organizing learning experience for the child care workers and parents such as field trip, child care training courses is important for the right prevention and control practices on prevention of communicable disease among children.